Influence of crop residues, matric potential and temperature on growth of Exserohilum turcicum an emerging maize pathogen in Argentina. (1st December 2018) - Montemarani, A.; Sartori, M.; Nesci, A.; Etcheverry, M.; Barros, G.
Abstract: Northern corn leaf blight (NCLB) caused by Exserohilum turcicum is an endemic foliar disease in the Argentinean maize production area. Before applying a control method, it is essential to focus on factors that lead to the survival and conservation of E. turcicum inoculum. However, there is little information about the life cycle of this emerging pathogen in our country. The objective of the present work was to analyse the growth ability of three E. turcicum isolates under different type and conditions of maize, wheat and soybean residues, matric potential, temperature and their interactions. Statistical analysis demonstrated a significant effect of three factors on growth rate: residues‐based media, matric potential and temperature. Among them the major effect was produced by matric potential followed by temperature. Although there were no significant differences in the growth rate among different residues types, the range of conditions in which growth occurred was different. According to these results, soybean residues would allow a better survival of E. turcicum inoculum under no‐tillage system and providing an inoculum source for maize infections in subsequent year. Significance and Impact of the Study: Exserohilum turcicum is an emerging pathogen in Argentina that has caused significant economic losses in different maize growing areas. However, at present there is a lack of information about the life cycle of this fungal pathogen. The present study shows the influence of abiotic factors such as temperature and water potential on the growth of E. turcicum on different crop residues used in rotations with maize under no‐till system cultivation. According to our results, soybean residues allowed the pathogen growth in a wider range of conditions compared to wheat and maize residue, providing an inoculum source for maize infections in subsequent season.